Analisis Kesiapan Teknologi dan Integrasi Sistem Bayraktar Dalam Mendukung Peran Strategis Puspenerbad - Arthur Agus Setiawan Idorway; Oktaheroe Ramsi; Sigit Purwanto (CV. Rayyan Dwi Bharata, 2026)
The development of increasingly complex global and regional threat dynamics, including the potential for asymmetric conflict and disruption to national sovereignty, demands increased readiness of the Indonesian Army's air units, especially Puspenerbad. The Bayraktar UCAV, as part of a modern weapons system, is an important strategy in facing these challenges. This research analyzes the technological readiness and integration of the Bayraktar TB2 system in supporting the strategic role of Puspenerbad, where the level of technological readiness of the Bayraktar TB2 faces the challenges of adapting to Indonesia's tropical conditions, and integration with the TNI AD's C4ISR architecture is hampered by data protocol incompatibility between the Bayraktar system and the TNI's legacy platform, requiring AI-based middleware for real-time interoperability. The aim of the research is to identify problems that affect Bayraktar's effectiveness in supporting Puspenerbad's main tasks and to provide recommendations for increasing Bayraktar's readiness in air defense operations. The research method is qualitative with case studies and literature studies. The results show that factors such as personnel mastery of Bayraktar technology, readiness of supporting logistics, and integration in military operations are crucial elements that influence the success of Bayraktar implementation. Budget limitations, lack of technical training, and lack of maintenance facilities are the main obstacles that must be overcome. Recommendations are directed at strengthening HR training policies, modernizing defense equipment, and increasing synergy between operational units and defense research institutions. Optimizing UCAV readiness is not only a technical matter but also a long-term strategy in maintaining sovereignty and strengthening the Indonesian Army's air defense posture in the modern era.